Bi-objective minimization of environmental impact and cost in utility plants - Martínez, P.; Eliceche, A.M. (Computers & chemical engineering, 2011)
► A methodology to minimize environmental impact and operating cost is presented. ► The operating conditions of a utility plant are selected. ► Different strategies are implemented to solve a bi-objective mixed-integer nonlinear programming problem. ► The economical valorization of the reduction of greenhouse gases emissions is evaluated. ► The Pareto points where this income compensates the increment in operating cost are identified. A methodology to minimize potential environmental impact and operating cost in the selection of the operating conditions of a steam and power plant is presented. A bi-objective mixed integer nonlinear programming problem is formulated and solved in GAMS. Different strategies are implemented successfully to generate the Pareto curve such as: minimum distance to the utopia point, ɛ-constraint, weighted sum and global criterion. An analysis of the Pareto curve allows the identification of two regions where it is cheaper and more expensive respectively, to reduce the potential environmental impact, providing relevant information to support a decision making process. The economical valorisation of greenhouse gases emissions reduction was also carried out, showing the region of the Pareto curve in which the income would compensate the increment in operating cost, leading to a reduction of the potential environmental impact with no extra cost.